2004
DOI: 10.1175/1520-0442(2004)017<3415:pmsotw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Polar MM5 Simulations of the Winter Climate of the Laurentide Ice Sheet at the LGM*

Abstract: Optimized regional climate simulations are conducted using the Polar MM5, a version of the fifth-generation Pennsylvania State University-NCAR Mesoscale Model (MM5), with a 60-km horizontal resolution domain over North America during the Last Glacial Maximum (LGM, 21 000 calendar years ago), when much of the continent was covered by the Laurentide Ice Sheet (LIS). The objective is to describe the LGM annual cycle at high spatial resolution with an emphasis on the winter atmospheric circulation. Output from a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(77 citation statements)
references
References 62 publications
5
72
0
Order By: Relevance
“…This points towards a feature caused by changes in atmospheric circulation. Bromwich et al (2004) suggested a split jet stream pattern around the Laurentide Ice Sheet during the LGM. Favourable transport north or south of the Laurentide during different time periods could possibly be an explanation for the feature observed here.…”
Section: Annual Layer Signaturementioning
confidence: 99%
“…This points towards a feature caused by changes in atmospheric circulation. Bromwich et al (2004) suggested a split jet stream pattern around the Laurentide Ice Sheet during the LGM. Favourable transport north or south of the Laurentide during different time periods could possibly be an explanation for the feature observed here.…”
Section: Annual Layer Signaturementioning
confidence: 99%
“…The area of LIS decreased to abut 2.0 × 10 6 km 2 during 6.0-7.0 BP and has remained nearly unchanged since then. Because the LIS can significantly alternate the surface energy balance of the high latitude North America (Bromwich et al 2004), the larger area of North America covered by LIS before 7.0 BP likely over- rode the effect of Atlantic SST, thereby weakening the relationship between the SST and drought.…”
Section: Statistical Relationship Between Atlantic Sst and Persistentmentioning
confidence: 99%
“…LGM cycles in the past 500 kyr are around 100 kyr (Hays et al, 1976;Imbrie and Imbrie, 1980); nevertheless, cycles between 80 and 120 kyr are not unusual (Huybers and Wunsch, 2005). During LGM the North American ice sheet was known to be dry (Bromwich et al, 2004); therefore, a constant LGM climate forcing beginning at an ice-free hemisphere takes longer to establish a fully grown North American ice sheet.…”
Section: Summary and Discussionmentioning
confidence: 99%